Spinal cord injury and physical activity: transforming rehabilitation - Galea, Mary (Henry Stewart Talks, 2012)
Spinal cord injury, An extreme example of forced inactivity, Deterioration of nervous and musculoskeletal systems, Role of exercise in reversing or preventing musculoskeletal deterioration, Comparative effectiveness research to evaluate rehabilitation after spinal cord injury